Comb-tailed spiders from Xishuangbanna, Yunnan Province, China (Araneae, Hahniidae) - Zhang, Zhi-Sheng; Li, Shuqiang; Zheng, Guo (Zootaxa, 2011)
Spiders of the family Hahniidae from the rainforest area of Xishuangbanna are examined. Totally 7 species, including 5 new species are reported: Alistra annulata sp. nov. (male), A. hippocampa sp. nov. (male, female), Hahnia saccata sp. nov. (male, female), H. submaginii sp. nov. (male, female) and H. senaria sp. nov. (male, female). Two known species, Hahnia flagellifera Zhu, Chen & Sha, 1989 (male, female) and H. himalayaensis Hu & Zhang, 1990 (male, female) are firstly recorded from Yunnan Province and redescribed here. The genus Alistra is firstly recorded from China. Morphological descriptions, illustrations and photos of all species are given. All specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences in Beijing (IZCAS).